Histopathological grading affects survival in patients with isocitrate dehydrogenase-wildtype gliomas - Hou, Ziming; Liu, Dongyuan; Hou, Zhe; Zhang, Hongbing; Wang, Hao (Frontiers in Oncology, 2025)
BackgroundThe World Health Organization (WHO) Classification of Tumors of the Central Nervous System (2021) defines lower-grade (WHO grade II/III) isocitrate dehydrogenase (IDH) wild-type astrocytoma as glioblastoma, IDH-wildtype, WHO grade 4. However, this definition is conditional. Notably, the traditional histopathological grade is no longer used, and the independent prognostic factor of tumor grade in IDH wild-type gliomas remains unclear. In this study, we aimed to determine if histopathological grade is an independent prognostic factor.MethodsThe clinical data and pathological information of 647 patients with IDH wild-type gliomas from the Chinese Glioma Genome Atlas (CGGA) database (2006-2019) were retrospectively analyzed. All patients were stratified according to histopathological grade and its prognostic significance in IDH wild-type gliomas. Univariate and Cox’s multivariate analyses were used to determine the prognostic significance.ResultsThe median follow-up time was 100.4 months, and the median survival time was 20.3 months. The histopathological grade was an important independent prognostic factor in the univariate and multivariate analyses, and a higher grade was associated with poor overall survival and progression-free survival. After further stratification by the extent of resection and postoperative adjuvant treatment, the histopathological grade remained a significant prognostic factor.ConclusionsIn this study, histopathological grade affected survival in IDH-wild-type gliomas. This effect appears to be independent of the extent of resection and postoperative treatment. Thus, we suggest that clinical treatment of patients with IDH wild-type gliomas should continue to consider histopathological grade along with the molecular characteristics of the tumors.